REGIONAL TAX LAW POLITICS IN THE ERA OF AUTONOMY FOLLOWING THE EFFECTIVENESS OF THE DECENTRALIZATION SYSTEM (Jurnal IUS Kajian Hukum dan Keadilan, 2013)
The decentralization system impacts the change of the local tax regulation. Based on  the Law No 34 of 2000 on local tax and retribution, local government may determine new kind of taxes  besides what  has established in this Law, but they must refer to the available criteria. Tax  as one of the important local incomes to finance either the government operation or local development and to support the accountable, real, and extant decentralization . After the Law No 34 of 2000 has been replaced by the law No 28 of 2009 on local tax and retribution, local government is not allowed to pick up tax other than what the law has determined. The basis of the tax and the discretion is extended.  To improve the tax accountability; this law stipulates that some parts of tax income should be allocated to finance activities relevant to such tax.Keywords : Local Tax